Management of injured patients who were Jehovah's Witnesses, where blood transfusion may not be an option: a retrospective review. Issue 3 (2nd February 2018) - Olaussen, A.; Bade‐Boon, J.; Fitzgerald, M. C.; Mitra, B.
Abstract : Introduction: Management of major haemorrhage as a result of trauma is particularly challenging when blood is not an option (BNAO). Evidence on therapeutic strategies in this situation is limited. The aim of this study was to evaluate the management and outcomes of patients who identified themselves as Jehovah's Witnesses (who usually refuse blood products) with traumatic haemorrhage at an Australian major trauma centre. Methods: A retrospective review of patients from The Alfred Trauma Registry was conducted, including patients who were Jehovah's Witnesses presenting between January 2010 and January 2017. We examined demographics, injury characteristics, clinical progress, therapeutic interventions and outcomes at hospital discharge. Results: There were 34 patients meeting inclusion criteria, with 50% suffering major trauma. Anaemia was a clinical problem for 13 (38·2%) patients, with haemoglobin levels reaching a nadir of 69·7 g/l (95% CI: 56·7–82·7) on average 5·1 days (95% CI: 2·5–7·7) post admission. Various strategies were employed to reduce blood loss including six (46·2%) patients receiving tranexamic acid, nine (29·2%) patients receiving oral or intravenous iron and five (38·5%) receiving erythropoietin. Three patients received packed red cells, and two patients received synthetic haemoglobin‐based oxygen carriers. Conclusions: Numerous therapeutic strategies were employed inconsistently in this unique population of patients. Augmenting circulatory volume with an oxygen carrier acceptable to JW patients presents a novel approach to be considered in adjunct to other strategies. An international resource centre would assist clinicians faced with anaemia and BNAO.